2007
DOI: 10.1111/j.1471-0528.2006.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine and breastfeeding—is it safe?

Abstract: Traditionally, women receiving azathioprine have been discouraged from breastfeeding because of theoretical potential risks of neonatal bone marrow suppression, susceptibility to infection, and pancreatitis. The aims of this study were to measure the concentration of 6-mercaptopurine (6-MP) in breast milk of mothers receiving azathioprine and in the blood of their babies and to investigate any immunosuppressive effects on the babies. Women receiving azathioprine, who after appropriate counselling wished to bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 9 publications
0
88
0
2
Order By: Relevance
“…Expert opinion differs regarding the use of azathioprine and 6-MP during lactation, but recent data support the view that these drugs may be prescribed on an individual basis and with caution during breastfeeding, as they are transmitted at very low levels in breast milk [74,75,76,77]. 6-Thioguanine concentration measurement offers a valuable means of objectively assessing infant exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Expert opinion differs regarding the use of azathioprine and 6-MP during lactation, but recent data support the view that these drugs may be prescribed on an individual basis and with caution during breastfeeding, as they are transmitted at very low levels in breast milk [74,75,76,77]. 6-Thioguanine concentration measurement offers a valuable means of objectively assessing infant exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of MP was 1.2 and 7.6 ng/mL, compared with the therapeutic immunosuppressant level of 50 ng/ mL in serum. 115 In a study of 11 mothers taking AZA during pregnancy and lactation compared with 12 patients without any immunosuppressive therapy, there was no increased risk of infections in babies exposed to AZA in utero and via breastfeeding. 116 The ECCO consensus supports that breastfeeding under maintenance AZA therapy could be advised for women who wish to nurse their infants.…”
Section: Decision-making Node #4: Breast Feedingmentioning
confidence: 97%
“…The risks and benefits of continuing treatment with thiopurines should be discussed with the mother 114,117 and the infants should receive continued monitoring and long-term assessment. 115,118 Corticosteroids. Corticosteroids are secreted into breast milk, and foetal levels are 10-12% of the maternal levels, depending on the steroid preparation.…”
Section: Decision-making Node #4: Breast Feedingmentioning
confidence: 99%
“…Several small studies have shown very low levels of drug excretion in breast milk that do not amount to clinically significant concentrations in the healthy breastfeeding infant [88][89][90]. Caution should be used in infants with compromised immune systems.…”
Section: Reviewmentioning
confidence: 99%